The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1080/23322039.2022.2103923
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of technical efficiency among youth involved in crop production in Njombe Region, Tanzania

Abstract: This study aimed to estimate the Technical Efficiency (TE) of youth crop farmers in Njombe Region of Tanzania, and analyze the determinants of technical inefficiency for crops produced. Data were collected from 572 youths in 16 villages of Njombe Region by using a random sampling technique. The Stochastic Production Function (SPF) model analysed technical efficiency among the youth crop farmers.Results show that youth crop farmers in the study region exhibited decreasing returns to scale, as confirmed by the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Besides, many studies also tend to focus on the impacts of youth (Ng'Atigwa et al, 2022;Song & Wang, 2015;Omorczyk et al, 2014;Hoc & Каракулова, 2010;Muhammad-Lawal, 2009) Bhat and Kaur (2022) showed that ageing of labor has a significant impact on mitigating the technical inefficiency of the Information Technology (IT) industry in India. Recently, the studies carried out by Ova (2023) proved that aging has a negative impact on inefficiency in textile industry of Czech Republic and Hungary.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many studies also tend to focus on the impacts of youth (Ng'Atigwa et al, 2022;Song & Wang, 2015;Omorczyk et al, 2014;Hoc & Каракулова, 2010;Muhammad-Lawal, 2009) Bhat and Kaur (2022) showed that ageing of labor has a significant impact on mitigating the technical inefficiency of the Information Technology (IT) industry in India. Recently, the studies carried out by Ova (2023) proved that aging has a negative impact on inefficiency in textile industry of Czech Republic and Hungary.…”
Section: Introductionmentioning
confidence: 99%